PENGARUH PEMBERIAN KOMPENSASI TERHADAP SEMANGAT KERJA KARYAWAN PT. PERKEBUNAN NUSANTARA V SEI GALUH KABUPATEN KAMPAR - Mestika Marisi; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aims to determine the effect of compensation on employee morale PT. PTPN V Sei Galuh Kampar district. Compensation as an independent variable (X) and morale as the dependent variable (Y), and respondents of this study took as many as 81 people. Data were obtained through questionnaires seloanjutnya processed for later tested through statistical analysis such as a simple regression analysis, t test, and correlation analysis and determination with the help of using SPSS.(1.990). This suggests that significant influental employee compensation employee morale. The amount of compensation the employee against employee morale PT. PTPN V Sei Galuh amounted to 55.4%.Keywords : Human Relationship, Compensation, Morale